Soil microbial community are more sensitive to ecological regions than cropping systems in alpine annual grassland of the Qinghai-Tibet Plateau - Luo, Feng; Mi, Wenbo; Liu, Wenhui; Ma, Xiang; Liu, KaiQiang; Ju, Zeliang; Li, Wen (Frontiers in Microbiology, 2024)
Modern agriculture emphasizes the design of cropping systems using ecological function and production services to achieve sustainability. The functional characteristics of plants (grasses vs. legumes) affect changes in soil microbial communities that drive agroecosystem services.Information on the relationship between legume-grass mixtures and soil microorganisms in different ecological zones guides decision-making towards eco-friendly and sustainable forage production. However, it is still poorly understood how cropping patterns affect soil microbial diversity in alpine grasslands and whether this effect varies with altitude. To fill this gap in knowledge, we conducted a field study to investigate the effects of growing oats (Avena sativa L.), forage peas (Pisum sativum L.), common cornflower (Vicia sativa L.), and fava beans (Vicia faba L.) in monocultures and mixtures on the soil microbial communities in three ecological zones of the high alpine zone. We found that the fungal and bacterial community structure differed among the cropping patterns, particularly the community structure of the legume mixed cropping pattern was very different from that of monocropped oats. In all ecological zones, mixed cropping significantly (P <0.05) increased the α-diversity of the soil bacteria and fungi compared to oat monoculture. The α-diversity of the soil bacteria tended to increase with increasing elevation (MY [2,513 m] < HZ [2,661 m] < GN [3,203 m]), while the opposite was true for fungi (except for the Chao1 index in HZ, which was the lowest). Mixed cropping increased the abundance of soil fungi and bacteria across ecological zones, particularly the relative abundances of Nitrospira, Nitrososphaera, Phytophthora, and Acari.Factors affecting the bacterial community structure included the cropping pattern, the ecological zone, water content, nitrate-nitrogen, nitrate reductase, and soil capacity, whereas factors affecting fungal community structure included the cropping pattern, the ecological zone, water content, pH, microbial biomass nitrogen, and catalase. Our study highlights the variation in soil microbial communities among different in alpine ecological regions and their resilience to cropping systems.Our results also underscore that mixed legume planting is a sustainable and effective forage management practice for the Tibetan Plateau.